Circadian-rhythm of the endopeptidase 22.19 (ec 3.4.22.19) in the rat-brain - Ferro, Emer S. [UNESP]; Sucupira, Mauro; Marques, Nelson; Camargo, Antonio C. M.; Menna-Barreto, Luiz (Marcel Dekker Inc, 1992)
The endopeptidase 22.19 (EC 3.4.22.19) has been associated with the metabolism of neuropeptides by its ability to convert small enkephalin-containing peptides (8 to 13 amino acids) into enkephalins. In addition, this enzyme cleaves the Arg8-Arg9 bond of neurotensin and the Phe5-Ser6 bond of bradykinin. We analyzed the circadian variation of endopeptidase 22.19 in the whole and individual areas of the rat brain. Endopeptidase 22.19 activity was analyzed by high-performance liquid chromatography (HPLC) using bradykinin as an operative substrate. Enzymatic specific activities were analyzed by rhythmometric methods and indicate a circadian fluctuation of endopeptidase 22.19 specific activity (mU of enzyme/mg of protein) in the whole brain [p < 0.001, mesor (M) = 7.62, amplitude (A) = 2.89, and acrophase (phi) = 23:08 h], striatum (p < 0.001, M = 2.92, A = 0.62, phi-23:03 h), hypothalamus (p < 0.001, M = 3.15, A = 0.86, phi-01:12 h), periaqueductal gray matter (p < 0.005, M = 2.62, A = 0.34, phi = 22:35 h), and cerebellum (p < 0.0 14, M = 4.27, A = 0.88, phi = 17:12 h). The circadian rhythmicity in endopeptidase 22.19 specific activity suggests that light may have an effect on the peptidase activity in whole brain and in areas of the central nervous system and may be essential for the mechanisms of circadian fluctuations of neuropeptides in the brain.
Keywords: CIRCADIAN RHYTHM; ENDOPEPTIDASE 22.19; EC 3.4.22.19; PEPTIDE METABOLISM; OPIOID PEPTIDES; ENKEPHALINS-RAT BRAIN